Global, regional, and national burden of glucose-6-phosphate dehydrogenase (G6PD) deficiency from 1990 to 2021: a systematic analysis of the global burden of disease study 2021 - Yu, Zhengyu; Xiong, Qiang; Wang, Zhongwang; Li, Linfeng; Niu, Ting (Frontiers in Genetics, 2025)
BackgroundGlucose-6-phosphate dehydrogenase (G6PD) deficiency remains a significant global health burden, particularly in malaria-endemic regions. Despite advances in diagnostic capabilities and treatment strategies, the prevalence and associated disability burden continue to evolve. This study provides a comprehensive assessment of the global, regional, and national burden of G6PD deficiency from 1990 to 2021, using the Global Burden of Disease (GBD) 2021 database.MethodsData were retrieved from GBD 2021, covering 204 countries and territories. Prevalence, incidence, and years lived with disability (YLDs) were analyzed. Age-standardized rates (ASRs) and estimated annual percentage change (EAPC) were computed to assess trends over time. The relationship between socio-demographic index (SDI) and G6PD burden was examined using Spearman correlation analysis.ResultsIn 2021, global prevalence reached 443,326,869 cases, an 80.17% increase from 1990. The highest burden was observed in South Asia, accounting for 138,159,940 cases. The largest percentage increase in prevalence was in Andean Latin America (+291.96%). G6PD deficiency burden was negatively correlated with SDI, but high SDI regions exhibited higher prevalence than expected. Age- and sex-specific analysis revealed a higher burden in males, particularly in childhood and older age groups.ConclusionThis study underscores the growing burden of G6PD deficiency, with substantial regional disparities. The findings emphasize the need for improved screening programs, policy interventions, and resource allocation in low- and middle-income countries (LMICs). Continued surveillance is essential to mitigate the long-term health consequences of this disorder.